LEGAL PROTECTION FOR INDONESIAN MIGRANT WORKERS: AN ANALYSIS OF ACCESSIBILITY IN DIVORCE - ganis vitayanty noor (Journal Philosophy of Law, 2023)
The Indonesian government strives to address the surge in unemployment through innovation via the Indonesian Migrant Worker Protection Agency (BP2MI), which directs the placement of Indonesian Migrant Workers. However, the impact of becoming Indonesian Migrant Workers is not always positive, especially for those who are married, as they are susceptible to divorce. This study aims to understand the impact and Indonesia's role in dealing with the consequences of Indonesian Migrant Workers. A socio-legal approach is employed through field interviews and observations. Findings indicate that migrant labor arises from weak economy, low education, and limited job opportunities. The positives include better employment prospects, higher income, new skills, and long-term benefits through remittances. Conversely, negatives involve divorce issues due to distance, infidelity, financial mismanagement, and other relationships. Legal and social protections are necessary, along with awareness of family impacts. While the Law Number 7 of 1989 concerning Religious Courts regulates divorce, complexities persist, necessitating streamlined administration, such as power of attorney legalization without involving embassies, to avoid clandestine divorce and administrative intricacies.